2013
DOI: 10.1007/s10802-013-9812-2
|View full text |Cite
|
Sign up to set email alerts
|

Affective, Biological, and Cognitive Predictors of Depressive Symptom Trajectories in Adolescence

Abstract: Heterogeneity in the longitudinal course of depressive symptoms was examined using latent growth mixture modeling among a community sample of 382 U.S. youth from ages 11 to 18 (52.1% female). Three latent trajectory classes were identified: Stable Low (51%; displayed low depressive symptoms at all assessments), Increasing (37%; reported low depressive symptoms at age 11, but then significantly higher depressive symptoms than the Stable Low class at ages 13, 15, and 18), and Early High (12%; reported high early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 55 publications
(90 reference statements)
7
58
1
3
Order By: Relevance
“…Parental depressive symptoms (Stoolmiller et al, 2005) and parental history of major depressive disorder (Yaroslavsky et al, 2013) were also predictive of higher symptom burden trajectories in adolescents. Other predictors of trajectories with high symptom burden in adolescents included lack of self-esteem (Costello et al, 2008), rumination (Mezulis, Salk, Hyde, Priess-Groben, & Simonson, 2014), loneliness, poor coping skills (Yaroslavsky et al, 2013) and early puberty (Mezulis et al, 2014). Means and odds ratios for most predictor variables followed a dose-response-like pattern, such that as the severity of the trajectory increased, so did the mean or odds ratio for that predictor variable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental depressive symptoms (Stoolmiller et al, 2005) and parental history of major depressive disorder (Yaroslavsky et al, 2013) were also predictive of higher symptom burden trajectories in adolescents. Other predictors of trajectories with high symptom burden in adolescents included lack of self-esteem (Costello et al, 2008), rumination (Mezulis, Salk, Hyde, Priess-Groben, & Simonson, 2014), loneliness, poor coping skills (Yaroslavsky et al, 2013) and early puberty (Mezulis et al, 2014). Means and odds ratios for most predictor variables followed a dose-response-like pattern, such that as the severity of the trajectory increased, so did the mean or odds ratio for that predictor variable.…”
Section: Resultsmentioning
confidence: 99%
“…Trajectories with higher depressive symptom burdens were frequently associated with subsequent psychiatric diagnoses: Stoolmiller et al (2005) and Mezulis et al (2014) found that adolescents in high depressive symptom trajectory classes were more likely to receive a diagnosis of major depressive disorder. Chaiton et al (2013) looked at the effect of depressive symptom trajectories in adolescents on mental health in young adulthood and found that the rate of diagnosed mood or anxiety disorders was 3 times as high among girls and twice as high among boys who experienced a depression trajectory in adolescence characterized by high symptom burden.…”
Section: Resultsmentioning
confidence: 99%
“…Childhood psychopathology is considered a major risk factor for psychopathology in adolescence and adulthood [13][14][15][16][17][18][19][20][21][22]. Adolescence has been defined as a vulnerable period for the onset of psychopathology, and brain and hormonal changes occurring during this period have been implicated in this growing vulnerability [23][24][25][26].…”
Section: Sleep and Psychopathology In Children And Adolescentsmentioning
confidence: 99%
“…gender) and general risk factors (e.g. social adversity) that predict membership in a high-risk latent class (Dekker et al, 2007; Mezulis, Salk, Hyde, Priess-Groben, & Simonson, 2013; Stoolmiller, Kim, & Capaldi, 2005). Below we review the evidence for specific predictors and outcomes of class membership focused mostly on pre-pubertal depression, including gender, social adversity, and functional outcomes later in life.…”
Section: Introductionmentioning
confidence: 99%
“…By early adolescence and continuing throughout adulthood, girls are more likely than boys to have membership in latent classes with more severe symptoms of depression (Brendgen, Wanner, Morin, & Vitaro, 2005; Costello, Swendsen, Rose, & Dierker, 2008; Mezulis et al, 2013). However, results are not as consistent during earlier childhood.…”
Section: Introductionmentioning
confidence: 99%